Moderating effects of body composition biomarkers on the relationship between thyroid hormones and cognitive performance in euthyroid older adults: insights from NHANES data - Li, Xiaosong; Duan, Hongliang; Liu, Shuang; Li, Hanyang; Zhang, Hong (Frontiers in Endocrinology, 2024)
Background Thyroid hormones are essential for cognitive function and can impact cognitive performance even in euthyroid individuals. This study investigates how thyroid hormones influence cognitive performance in the elderly and whether body composition biomarkers moderate this relationship. The aim is to determine if lifestyle interventions should prioritize weight loss, overall body fat reduction, or abdominal fat loss. Methods We analyzed data from the NHANES 2011-2012 dataset, focusing on thyroid hormone levels, cognitive performance, and body composition metrics in euthyroid individuals aged 60 to 80 years. A total of 573 participants were included in the analysis. Pearson correlation analyses were conducted to evaluate the associations between thyroid hormone indicators and cognitive performance metrics. Ordinal logistic regression and linear regression analyses were used to determine the predictive capacity of thyroid hormones on cognitive functions, adjusting for potential confounders such as age, gender, and education level. Statistical analyses were performed using R Studio and Stata, utilizing Pearson correlation, ordinal logistic regression, and linear regression methods. Results Significant correlations were observed between short-term memory and TT3 (r = 0.111, p = 0.018), TSHI (r = -0.121, p = 0.010), and TFQI (r = -0.107, p = 0.023); delayed memory and FT3 (r = 0.143, p = 0.003), TT3 (r = 0.146, p = 0.002), and TSHI (r = -0.125, p = 0.009); and executive function with FT4 (r = -0.141, p = 0.003) and the FT3/FT4 ratio (r = 0.137, p = 0.004). Although thyroid indicators did not independently predict short-term memory (OR = 0.006, p = 0.116), they were statistically significant for delayed memory with FT3 (OR = 0.642, p = 0.017) and TT3 (OR = 0.010, p = 0.015). Linear regression analysis indicated that FT4 (t = -2.99, p = 0.003) and the FT3/FT4 ratio (t = 2.91, p = 0.004) were significant predictors of executive function. Hierarchical regression analyses revealed that BMI and waist circumference (WWI) significantly moderated the relationship between thyroid function and short-term memory (BMI: z = 2.44, p = 0.015; WWI: z = -2.19, p = 0.029). BMI also moderated the models for delayed memory (z = 2.11, p = 0.035), while RFM and C-index did not exhibit significant moderating effects. No moderators were identified in the relationship between executive function and thyroid hormones. Conclusion This study underscores the significant influence of higher BMI and waist circumference on the relationship between thyroid function and memory performance. In contrast, body composition indicators such as RFM and C-index do not appear to significantly affect cognitive function related to thyroid levels, highlighting the importance of fat distribution in cognitive health assessments.